FRUSTRATION AS A FORMING FACTOR OF AGGRESSIVE BEHAVIOR IN MOSLEM ADOLESCENTS IN PLAYING ONLINE GAMES - Wahyu Ade Nugroho; Fani Reza, Iredho (CV. Era Digital Nusantara, 2022)
This study aims to determine the relationship between frustrated with aggressive behavior in moslem adolescents in playing games online. This research method is correlational quantitative. The subject of this research are students. The sampling technique that used in this study is a simple random sampling technique using Isaac and Michael's formula with an error rate of 5% with a sample of 90 students. The instrument used is a frustration and aggressive behavior scale. Results of data analysis with the Pearson Product Moment correlation (with the help of SPSS version 25 for Windows) shows a positive and significant relationship between frustration and aggressive behavior on students playing online games, r = 0.481 with p = 0.000. This means that with the results of this study, it can be the key word is frustrated in students playing games, the higher the aggressive behavior on the students play online games and vice versa. And an effective of determination of 0.232 contributes to the influence of aggressive behavior by 23.2% while the rest, 76.8% is influenced by other factors that can affect aggressiveness.